An evolutionary view of economic growth Ashok S. Guha.. - Guha, Ashok S. (Clarendon Press: Oxford University Press, 1981)
This is a bold book drawing not only on economics and history but also on anthropology and ethology. It is about the survival of the fittest economic societies. The theme of the book is that economic growth is an extension of organic evolution. Growth is best interpreted as the adaptation of structures inherited from the best interpreted as the adaptation of structures inherited from the past - whether political, economic, social or psychological - to the pressures of a changing environment.